(untitled) (Journal of Geography and Environmental Management, 2019)
The article considers the prospects and problems of development of business tourism in the Almaty City. The advantageous and disadvantageous factors that adversely affect to the development of business tourism are shown. Analysis of business tourism state is based on statistical data.